2007
DOI: 10.1016/j.devcel.2007.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Mechanisms of Border Cell Migration Analyzed Using Time-Lapse Live-Cell Imaging

Abstract: Border cells in the Drosophila ovary originate within an epithelium, detach from it, invade neighboring nurse cells, and migrate as a coherent cluster. This migration has served as a useful genetic model for understanding epithelial cell motility. The prevailing model of growth factor-mediated chemotaxis in general, and of border cells in particular, posits that receptor activation promotes cellular protrusion at the leading edge. Here we report the time-lapse video imaging of border cell migration, allowing u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
281
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(293 citation statements)
references
References 41 publications
11
281
1
Order By: Relevance
“…SlboGal4, UAS-dsRedNLS; UASmoesinGFP, and slbo-Lifeact-GFP flies were used for live imaging and were described before (26,29). UAS-PVR DN , UAS-EGFR DN , and UAS-EcadRNAi (VDRC: KK103962) were described previously (23,24,26,29).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SlboGal4, UAS-dsRedNLS; UASmoesinGFP, and slbo-Lifeact-GFP flies were used for live imaging and were described before (26,29). UAS-PVR DN , UAS-EGFR DN , and UAS-EcadRNAi (VDRC: KK103962) were described previously (23,24,26,29).…”
Section: Methodsmentioning
confidence: 99%
“…During migration, the cells respond to at least four secreted factors produced in the germ line: PDGF-and VEGF-related factor 1 (PVF1), which binds to and activates its receptor (PVR), as well as Spitz, Keren, and Gurken (Grk), which bind and activate epidermal growth factor receptor (EGFR), which like PVR is a receptor tyrosine kinase. Inhibiting both receptors in the border cells at the same time causes the cells to migrate poorly and sometimes off-track (23)(24)(25)(26). It would be interesting to directly measure the spatial profiles of the ligands; however, antibodies are only available against PVF1 and Grk, and the extracellular protein is not abundant enough to detect.…”
mentioning
confidence: 99%
“…This attachment provides an inherent polarity for each cell, as intracluster cell interactions are distinguishable from interactions with the nurse-cell substrate. Live imaging has shown border cell migration to be very dynamic, with cells exchanging places frequently (9,10). Border cells are directed by guidance cues from the oocyte and use two RTKs (PVR and EGFR) to read these cues (12,13).…”
mentioning
confidence: 99%
“…The system is genetically tractable and allows live imaging in the tissue, making it a good model for studying collective cell migration (9,10). Once specified, border cells delaminate from the follicular epithelium, invade the underlying germ line tissue, and migrate between the giant nurse cells to the oocyte.…”
mentioning
confidence: 99%
“…As these organisms are thinner and smaller than mammals and also relatively easy to manipulate, better resolution can be achieved with spinning-disc or conventional confocal microscopy. Recent studies of border and immune cells in Drosophila, and neurons in zebrafish have revealed exciting new information regarding cell migration and adhesion within intact organisms and the signalling mechanisms responsible for driving these events (Bianco et al, 2007;Koster and Fraser, 2001;Prasad and Montell, 2007;Robles and Gomez, 2006;Stramer et al, 2005).…”
Section: Visualising Adhesions In Whole Organismsmentioning
confidence: 99%